PERAN GURU DALAM MEMBANGUN REPUTASI SEKOLAH MELALUI KOMUNIKASI ORGANISASI - Sinta Paramita; Riris Loisa; Yugih Setyanto (Jurnal Bakti Masyarakat Indonesia, 2021)
Problems related to organizational communication climate are still a severe problem in Indonesia. Cases related to conflict problems in various organizations occur at multiple levels, ranging from small organizations or institutions to rice, including educational institutions. By creating an atmosphere of an excellent organizational communication climate, educational services such as learning, and others can make the school's image and reputation. Therefore, the Fikom Untar PKM Team strives to help schools build a good reputation in organizational communication. The theme raised by the Fikom Untar PKM Team was "The Role of Teachers in Building School Reputation through Organizational Communication," which will be implemented at Lia Stephanie School, West Jakarta, which is considered to be able to help solve problems faced by schools. The method used in solving this problem is to map the problem and provide the right solution. The results obtained from these activities, the participants know and understand the understanding of internal communication principles, how to build a corporate image, and the elements of organizational culture, by increasing knowledge of organizational communication, it is hoped that a good organizational communication climate can be created.ABSTRAK:Masalah terkait iklim komunikasi organisasi masih menjadi persoalan yang serius di Indonesia. Kasus-kasus terkait masalah konflik dalam organisasi jamak terjadi di berbagai level baik organisasi atau institusi dalam cakupan kecil hingga beras termasuk institusi pendidikan seperti sekolah. Dengan menciptakan suasana iklim komunikasi organisasi yang baik, pelayanan pendidikan seperti pembelajaran dan lain-lain dapat menciptakan citra dan reputasi bagi sekolah tersebut. Oleh sebab itu Tim PKM Fikom Untar berupaya membantu sekolah dalam membangun reputasi yang baik dalam komunikasi organisasi. Tema yang diangkat oleh Tim PKM Fikom Untar adalah “Peran Guru Dalam Membangun Reputasi Sekolah Melalui Komunikasi Organisasi” yang akan dilakukan di Sekolah Lia Stephanie Jakarta Barat, dirasa dapat membantu dalam menyelesaikan masalah yang dihadapi sekolah. Metode yang digunakan dalam menyelesaikan masalah ini adalah dengan melakukan pemetaan permasalahan dan memberikan solusi yang tepat. Hasil yang diperoleh dari kegiatan tersebut peserta mengetahui dan memahami terkait pemahaman asas komunikasi internal, cara membangun citra organisasi, dan elemen budaya organisasi, dengan meningkatnya pemahaman terkait komunikasi organisasi diharapkan dapat menciptakan iklim komunikasi organisasi yang baik.